The expulsion of the different. Discipline, sanitation, and illness in “Lorenzita” by Manuel Atanasio Fuentes - Leonardo-Loayza, Richard (2022)
The article analyzes “Lorenzita” (1898) by Manuel Atanasio Fuentes, a text that can be considered as the first literary manifestation that addresses the issue of sexual dissidence in Peru. An attempt is made to show that this text shows the rejection of the leadership élites regarding the body of the homosexual, which is considered a sick and abject body. This position is related to the disciplining and sanitation practices that this élite develops against the identities that it is thought should not be included in the modernization projects of the Peruvian nation at the end of the 19th century.